If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5t + (2 + -2t) = 3 Remove parenthesis around (2 + -2t) -5t + 2 + -2t = 3 Reorder the terms: 2 + -5t + -2t = 3 Combine like terms: -5t + -2t = -7t 2 + -7t = 3 Solving 2 + -7t = 3 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -7t = 3 + -2 Combine like terms: 2 + -2 = 0 0 + -7t = 3 + -2 -7t = 3 + -2 Combine like terms: 3 + -2 = 1 -7t = 1 Divide each side by '-7'. t = -0.1428571429 Simplifying t = -0.1428571429
| -10/7+10 | | -6(4u-1)+3u=-3(u+3) | | 163=4k+3(1-8k) | | x-7=5x-7 | | -6=-6x+6(2x-13) | | (x^2+9)+(6x)=100 | | -24+6v=v-9 | | 3+3n-8n=-7 | | -9=5q/2-1/4(-6q+4) | | 163=4x+3(1-8k) | | 30x=6x-54 | | 5/3+17/6 | | 7a-9=-19+6a | | 110+.40x=30+.80x | | 8v+v=9 | | 4y+2y=48 | | 45y^3z^10/5y^3z | | f(x)=7x^2-4x | | k-1/3(1-9k)=2/3 | | y=2x-1forx | | 22-8m=-8m-11m | | 9+6m=45 | | -4-6n=5-9n | | (m^5n)^-2/m^-2n^3 | | x+3+3x-(6)=180 | | 1.2-0.3m=1.8 | | z(z^2+1)=5+z^3 | | 1=k+8/15 | | 6/7*9/16 | | -7k-k=-10k | | -116=-7x+2(-7x+5) | | 4.8/3 |